Frailty as a Predictor of Mortality in Patients With Interstitial Lung Disease Referred for Lung Transplantation. Issue 4 (April 2020) - Montgomery, Elyn; Macdonald, Peter S.; Newton, Phillip J.; Chang, Sungwon; Jha, Sunita R.; Hannu, Malin K.; Thomson, Claire; Havryk, Adrian; Malouf, Monique
Abstract : Background: Frailty is a clinically recognized syndrome of decreased physiological reserve and a key contributor to suboptimal clinical outcomes in various lung disease groups. Interstitial lung disease (ILD) is fast approaching chronic obstructive pulmonary disease as the number one indication for lung transplantation worldwide. Our aim was to assess whether frailty is a predictor of mortality in patients with ILD referred for lung transplantation in an Australian cohort. Methods: Consecutive patients with ILD referred or on the waiting list for lung transplantation from May 2013 to December 2017 underwent frailty assessment using the modified Fried's frailty phenotype. Frailty was defined as a positive response to ≥3 of the following 5 components: weak grip strength, slowed walking speed, poor appetite, physical inactivity, and exhaustion. Results: One hundred patients (82 male:18 female; age, 59 ± 7 y; range, 30–70) underwent frailty assessment. Twenty-four of 100 (24%) were assessed as frail. Frailty was associated with anemia, hypoalbuminemia, low creatinine, and the use of supplemental oxygen (all P < 0.05). Frailty was independent of age, gender, measures of pulmonary dysfunction (PaO2, forced vital capacity percentage predicted, total lung capacity, total lung capacity percentage predicted, DLCO, or DLCO percentage predicted), cognitive impairment, or depression. Frailty and DLCO % predicted were independent predictors of increased all-cause mortality: 1-year actuarial survival was 86 ± 4% in the nonfrail group compared with 58 ± 10% for the frail group ( P = 0.002). Conclusions: Frailty is common among patients referred for lung transplant with a diagnosis of ILD and is associated with a marked increase in mortality.